A primer on cytokines. (September 2021) - Chauhan, Prashant; Nair, Arathi; Patidar, Ashok; Dandapat, Jagneshwar; Sarkar, Arup; Saha, Bhaskar
Abstract: Cytokines are pleiotropic polypeptides that control the development of and responses mediated by immune cells. Cytokine classification predominantly relies on [1] the target receptor(s), [2] the primary structural features of the extracellular domains of their receptors, and [3] their receptor composition. Functionally, cytokines are either pro-inflammatory or anti-inflammatory, hematopoietic colony-stimulating factors, developmental and would healing maintaining immune homeostasis. When the balance in C can form complex networks amongst themselves that may affect the homeostasis and diseases. Cytokines can affect resistance and susceptibility for many diseases and their availability in the host cytokine production and interaction is disturbed, immunopathogenesis sets in. Therefore, cytokine-targeting bispecific, and chimeric antibodies form a significant mode of immnuo-therapeutics Although the field has grown deep and wide, many areas of cytokine biology remain unknown. Here, we have reviewed these cytokines along with the organization, signaling, and functions through respective cytokine-receptor-families. Being part of the special issue on the Role of Cytokines in Leishmaniasis, this review is intended to be used as an organized primer on cytokines and not a resource for detailed discussion- for which a two-volume Handbook of cytokines is available- on each of the cytokines. Priming the readers on cytokines, we next brief the role of cytokines in Leishmaniasis. In the brief, we do not provide an account of each of the involved cytokines known to date, instead, we offer a temporal relationship between the cytokines and the progress of the infection towards the alternate outcomes- healing or non-healing- of the infection.